Malay artists and the postmodern situation: thematic approaches since the 1990s - Abdullah, Sarena (RogueArt, 2013)
1his essay discusses thematic approaches taken by Malay artists in Malaysia since the 1990s. Malaysian art has become increasingly diverse in terms of its approaches, subjects, themes and media. This growing artistic diversity is discussed within a postmodern framework and is representative of a shift in tendencies away from a purely Malay/Islamic-centred artistic tradition to a more postmodern approach. Since the 1990s, works produced by Malay artists have taken a more critical perspective aligned with the postmodern situation or situasi percamoden, in accordance with Malaysia's leapfrog into modernisation. Through their works, Malay artists raise concerns and issues pertaining to the consequences of development and modernisation, and explore themes ranging from social problems, to the environment and urbanisation, and other contemporary issues, employing postmodernist approaches in their art. What is obvious is that Malay artists are concerned with the immediate and near future, rather than looking back or glorifying the past. These artistic tendencies epitomise the challenges, divergences and shared perspectives that define the growing Malaysian middle class especially in the context of the construction or even deconstruction of Malaysian society.